Application of innovation platforms to catalyse adoption of conservation agriculture practices in South Asia. Issue 4 (4th July 2022) - Brown, Peter R.; Anwar, Mazhar; Hossain, Md. Shakhawat; Islam, Rashadul; Siddquie, Md. Nur-E.-Alam; Rashid, Md. Mamunur; Datt, Ram; Kumar, Ranvir; Kumar, Sanjay; Pradhan, Kausik; Das, K. K.; Dhar, Tapamay; et al.
ABSTRACT: Conservation agriculture-based sustainable intensification (CASI) is a package of practices that could improve the sustainability of smallholder farm productivity and profitability. However, existing extension systems are unable to facilitate widespread adoption to have the impact necessary to meet food security and livelihood requirements. This paper examines the utility of 'Innovation Platforms' (IPs) as a tool to catalyse adoption of CASI for smallholder farmers in South Asia and generate opportunities for rural micro-entrepreneurship in areas with high rates of poverty, small farm sizes and complex labour markets. We established 37 village-level and five District-level IPs across the Eastern Gangetic Plains of Nepal, Bangladesh, and India. IPs allowed widespread uptake of CASI with benefits to smallholder farmers, input and output suppliers, and enabled extension systems to be more efficient. There was variability across locations with different modes of IPs established, building on existing farmer or community youth groups, and enabling micro-entrepreneur business opportunities. IPs were effective in developing trust in communities, among stakeholders, empowering rural youth and women through direct engagement. Ensuring strong ownership was key. Further work is needed to provide opportunities for high-level policy support to assist IPs to have a wider impact in supporting large-scale adoption of CASI.